Research Trends on the Use of Artificial Intelligence in Islamic Religious Education: A Systematic Review from 2021 to 2025 - Ikhsan Ikhsan; Mudayat Mudayat; Ichwan Ichwan; Elpipres Niku (GHAITSA : Islamic Education Journal, 2026)
This study investigates research trends on the use of Artificial Intelligence (AI) in Islamic Religious Education (IRE) from 2021 to 2025. A systematic review methodology was employed following PRISMA 2020 guidelines, resulting in the inclusion of 34 peer-reviewed Scopus-indexed articles. The findings reveal that quantitative research approaches, particularly experimental and quasi-experimental designs, dominate the field. Higher education institutions serve as the primary research settings, while studies at the madrasah, Islamic boarding school (pesantren), and early childhood Islamic education levels remain underrepresented. The primary purposes of AI integration identified in the literature center on enhancing learning outcomes, personalizing instruction, and supporting assessment in educational contexts applicable to IRE. Most studies recommend broader AI adoption accompanied by strong ethical frameworks, teacher training, and institutional support recommendations directly relevant to the development of Islamic Religious Education learning environments. This review highlights a critical gap: very few studies explicitly contextualize AI integration within IRE settings, suggesting a significant opportunity for research that integrates Islamic values and pedagogical principles with AI-driven educational innovations. Findings provide a roadmap for Islamic education researchers, madrasah administrators, and IRE curriculum developers seeking to leverage AI responsibly and equitably